2017
DOI: 10.1158/1535-7163.mct-16-0606
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Growth and Invasion of Human Head and Neck Squamous Cell Carcinomas via Regulating STAT3 Signaling and the miR-21/β-catenin Axis with HJC0152

Abstract: Signal transducer and activator of transcription 3 (STAT3) is involved in the tumor growth and metastasis of human head and neck squamous cell carcinoma (HNSCC) and is therefore a target with therapeutic potential. In this study, we show that HJC0152, a recently developed anticancer agent and a STAT3 signaling inhibitor, exhibits promising antitumor effects against HNSCC both in vitro and in vivo via inactivating STAT3 and downstream microRNA-21/β-catenin axis. HJC0152 treatment efficiently suppressed HNSCC ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 51 publications
4
29
0
1
Order By: Relevance
“…Our previous studies and a report from other groups have shown that STAT3 is a primary target of HJC0152 in breast cancer, head and neck squamous cell carcinoma, glioma, and gastric cancer . In this study, we showed that STAT3 expression is a prognostic factor for NSCLC patients (Figure A‐C), and that STAT3 is activated in NSCLC cells (Figure D and E).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Our previous studies and a report from other groups have shown that STAT3 is a primary target of HJC0152 in breast cancer, head and neck squamous cell carcinoma, glioma, and gastric cancer . In this study, we showed that STAT3 expression is a prognostic factor for NSCLC patients (Figure A‐C), and that STAT3 is activated in NSCLC cells (Figure D and E).…”
Section: Resultssupporting
confidence: 74%
“…The lysates were then centrifuged (13 000 × g , 4°C) for 15 minutes to obtain total protein lysates. Protein expression was analysed using Western blotting as described previously . The expression level of GAPDH was used as the loading control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their data suggested that the activation of Nanog/STAT3 signaling participated in this miR-21 production. In conformity with this result, it has been shown that inhibition of nuclear translocation of phosphorylated STAT3 abrogated the downstream miR-21/β-catenin axis, leading to suppression of tumor growth and invasion in HNSCC [59].…”
Section: Microrna-21supporting
confidence: 57%
“…CAFs have also been shown to enhance the metastatic potential of lung cancers via IL-6/STAT3 signalling pathways [40]. Importantly, studies associated with STAT3 also showed its involvement in enhancing the tumor growth and metastasis of human head and neck squamous cell carcinoma (HNSCC) [41]. In agreement, as described in Supplementary Figure S1, when STAT3 was silenced, CAL27 and SCC-15 cells lost a significant degree of ability to generate tumor spheres and the EVs released from STAT3-silenced tumor spheres, contained a lower level of β-catenin, TGFβ1 and miR-21-5p; these observations strongly suggest that inhibiting signaling networks such as STAT3/β-catenin, associated with the generation of cancer stem cells, could lead to the reduced oncogenic cargos released into the TME.…”
Section: Discussionmentioning
confidence: 99%